Recent Advances in Risk Management Using Business Intelligence (International Journal of Innovative Research in Engineering & Management, 2023)
Over the last several decades, risk  supervision has been a hot subject in both academic world and practice. The complexity of the company and the  environment inwhich it works determine operational risk.  As the company or the environment becomes more  dynamic, i.e., where change is a constant characteristic  and a factor to consider into the management of the firm,  such complexity grow. The important issue companies react to such changes today, and what measures can businesses take to anticipate and prepare for  change as the nature of business and the environment  becomes more dynamic. The majority of business  intelligence (BI) programs or software have been utilized  to improve risk supervision, and business intelligence  methods have improved risk management solutions. This  introductory paper offers an overview of current business  intelligence research in risk management.
Keywords: Business Intelligence; Risk Supervision; Operations Research